Privileging the Decolonial Critical Theory in studying wa Thiong’o’s literary works (Journal of Decolonising Disciplines, 2021)
Literary theories are the lens in which reality is created and viewed. If an incorrect or limited lens in used, then they impact on vision hence the corrective lenses are used to correct impaired vision. The literary works of Ngugi wa Thiong’o have been comfortably viewed from Marxist, Nationalist and Post-colonialist lens. It is the argument of this paper that though these literary theories do shed clarity on the works of wa Thiong’o, they limit the span of what we see that is outside their frames. The paper privileges the Decolonial Critical Theory, a theory located in the Global South, as the most appropriate lens to visibilise the decolonial thoughts and philosophy of wa Thiong’o. The appropriateness of the Decolonial Critical Theory is that it provides   a critical lens outside the Euro- North American “mainstream” canon foregrounded in coloniality. The argument expanded here is that essentialisms and fundamentalisms like Marxism, Nationalism and Post-colonialism are limited in the critique of wa Thiong’o as they do not take coloniality and decoloniality into account. Undoubtedly,  wa Thiong’o has been many things politically and philosophically, but decoloniality as a philosophy is the organising idea and overarching line of his thought. Like decoloniality itself, wa Thiong’o has developed, journeyed and passed through different ideological and philosophical liaisons to arrive at his present decolonial consciousness and activism hence Decolonial Critical Theory is a betting lens in looking at this journey.
Keywords: Decoloniality; Marxism; Nationalism; Post-colonialism